The association between dolutegravir based first-line antiretroviral regimens and dyslipidemia among adults living with HIV on follow-up at health facilities in Hawassa city administration, Sidama region: a cross-sectional study - Agete Tadewos Hirigo; Alemayehu Abera; Daniel Yilma; Ayalew Astatkie; Zelalem Debebe (Atherosclerosis Plus)
Background: Inconsistent evidence on lipid alterations in people living with HIV (PLWH) on dolutegravir (DTG)-based antiretroviral therapy (ART) highlights the need for further study. This study aimed to assess the association between DTG-based regimens and dyslipidemia among adults initiated on ART after the test-and-treat implementation in Ethiopia. Methods: A cross-sectional study was conducted in Hawassa City Administration, Sidama region, southern Ethiopia from January 2023 to May 2024. Participants were selected using systematic random sampling. Sociodemographic, clinical, and other relevant data were collected using a semi-structured questionnaire, supplemented by a review of medical records. Dyslipidaemia was classified based on the NCEP ATP III guidelines. A binary logistic regression model was fitted to identify factors associated with dyslipidemia. An adjusted odds ratio (aORs) and 95 % confidence intervals (CIs) were computed to determine the strength of the association, with statistical significance set at p < 0.05. Results: Of the 465 eligible adults, 450 participated in the study, attaining a response rate of 96.8 %. Of these, 262 (58.2 %) were female. Overall, 74.0 % (95 % CI: 69.8 %–78.0 %) of participants had dyslipidemia, with a higher prevalence in males (79.8 %) than in females (69.8 %). Low HDL-cholesterol was the most common lipid abnormality (66.4%), followed by high triglyceride and elevated total cholesterol/HDL-cholesterol ratio (each 34.2 %). ART initiation with DTG-based first-line regimen (aOR: 4.8; 95 %CI: 1.2–18.5), increased waist circumference (aOR: 1.06; 95 %CI: 1.01–1.11) and neck circumference (aOR: 1.2; 95 %CI: 1.06–1.5) were significantly associated with dyslipidemia. Conclusion: Based on the study findings, we recommend that routine lipid monitoring be integrated into the clinical management of PLWH on ART, to enable early detection and timely intervention for dyslipidemia.